Law no 79/2016 on settlement of tax disputes = قانون رقم 79 لسنة 2016 في شأن إنهاء المنازعات الضريبية - Egypt. Ministry of trade and industry. The Egyptian Customs Authority (2025)
Law no. 79 of the year 2016 on settlement of tax disputes – قانون رقم 79 لسنة 2016 فى شأن إنهاء المنازعات الضريبية